Glycemic control in non-critically hospitalized patients in tertiary hospitals in northeast Brazil - Janja, Matheus Mendonça Leal; Regadas, Carolina Murad; Ximenes, Fernando Antônio Mendes Bezerra; Andrade, Talita Guimarães; Vasconcelos, Melina Maria Loiola Melo; Castelo, Maria Helane Gurgel; Ponte, Clarisse Mourão Melo (Journal of Health & Biological Sciences, 2021)
Objective: Inpatient glycemic control is considered an important component of hospital care and patient safety. Nevertheless, its importance in the hospital setting is often underestimated. We aimed to evaluate glycemic control in non-critically hospitalized patients in the state of Ceará, in Northeast Brazil. Methods: A cross-sectional study was conducted in three tertiary hospitals in the state of Ceará. We evaluated non-critically ill inpatients, aged 18 years or older, who had hyperglycemia during hospitalization (random plasma glucose > 140 mg/dL or self-reported diabetes mellitus [DM]). Results: We evaluated 136 patients (66.2% male, mean age 57.9 ± 16.6 years), 64% of whom had a prior DM diagnosis. Specific nutritional support for DM or hyperglycemia was prescribed for 59.6% of patients. In total, 69.9% of the patients were using insulin. Among them, 47.4% used sliding-scale regular insulin, 18.9% basal-bolus (neutral protamine Hagedorn [NPH] insulin), 28.4% basal-plus (NPH) and 3.1% basal insulin (NPH). The prescriptions given were considered adequate for 26.4% of patients. Of the patients, 69.9% presented blood glucose levels > 180 mg/dL and 29.4% presented levels > 300 mg/dL. Hypoglycemia was observed in 25.7% of patients; protocols for hypoglycemia management were prescribed for 76.5% of them. Education on diabetes during hospitalization was reported by 30.1%. Conclusion: The glycemic control regime followed neither national nor international guidelines. These data suggest a need for teams of diabetes specialists in public hospitals in Ceará, working to improve care and following protocols to guide the safety of hospitalized patients.